Regulatory Environmental Impact, Contract Law, Intellectual Property Rights, and Taxation of Entrepreneurial Activities in Bandung City - Anis Okta Cahyaningrum; Riko Mersandro Permana; Arief Yanto Rukmana; Suroso Suroso; Fachrurazi Fachrurazi (Jurnal Ekonomi dan Kewirausahaan West Science, 2023)
This study investigates the regulatory environment impacting entrepreneurial activities in Bandung City, focusing on environmental impact, contract law, intellectual property rights, and taxation. The study employs a mixed-methods approach, including a survey of 100 entrepreneurs and interviews with key stakeholders. The results indicate that entrepreneurs in Bandung City face significant challenges in complying with environmental impact regulations, protecting their intellectual property rights, and navigating the complex tax system.These challenges can significantly impact the success of entrepreneurial activities and discourage entrepreneurship in the region. The study identifies several strategies for supporting entrepreneurial activities in Bandung City, including improving the clarity and consistency of regulations, enhancing awareness and understanding of intellectual property rights, and simplifying the tax system. Policymakers could also explore other strategies, such as providing training and support for entrepreneurs on regulatory compliance and intellectual property management. The study highlights the need for policymakers to balance the benefits of regulation with the potential burdens on entrepreneurial activities and adopt a more entrepreneurial mindset in designing policies that support innovation and economic growth.